Edukasi Pola Asuh dan Gizi Seimbang untuk Mengurangi Risiko Stunting pada Balita di Lubuk Tukko: Pengabdian - Suri Hariyatih; Zahra Amalia Khairai; Muhammad Iqbal Rahman; Ahmad Maulid Nasution; Mhd. Yadi Harahap (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Stunting is a chronic nutritional problem that remains a major public health challenge in Indonesia. The main factors causing stunting are inappropriate parenting practices and limited fulfillment of balanced nutrition. Based on data from the local Public Health Center, out of 102 toddlers measured, 99% have a normal height, while the remaining 1% are in the very short category. Through the Community Service Program (KKN), students of Universitas Islam Negeri Sumatera Utara (UINSU) carried out an educational activity on parenting practices and balanced nutrition in Lubuk Tukko Village on August 7, 2025. The methods used included interactive counseling, discussions, and collaboration with the village government, which also provided free nutritious food. The results showed an increase in community understanding, with around 80% of participants able to recall the main points regarding stunting and the importance of balanced nutrition. The activity also proved effective in raising community awareness and encouraging the adoption of healthy living behaviors as a tangible effort to reduce the stunting rate.